A Persian View of the Steppe Iranians - Borjian, Habib (Anabasis. Studia Classica et Orientalia, 2014)
The intention of this paper is to give a broad outline of the persistent presence of the Steppe Iranians in the Persian history and culture, by bringing together two fields that have often been treated independently. After an overview of the history of interactions between Persia and the Iranian-speaking Steppe nomads, we will extend our attention to the Iranian national history to offer some insights on myths and legends of the Shahnama that have been originated from or influenced by the mutual relations between the Steppe nomads and the dynasties who ruled on the Iranian Plateau.